The Xanthomonas type IV pilus - Dunger, Ricardo German (2016)
Type IV pili, a special class of bacterial surface filaments, are key behavioral mediators for many important human pathogens. However, we know very little about the role of these structures in the lifestyles of plant-associated bacteria. Over the past few years, several groups studying the extensive genus of Xanthomonas spp. have gained insights into the roles of played by type IV pili in bacteria-host interactions and pathogenesis, motility, biofilm formation, and interactions with bacteriophages. Protein-protein interaction studies have identified T4P regulators and these, along with structural studies, have begun to reveal some of the possible molecular mechanisms that may control the extension/retraction cycles of these dynamic filaments.